[PP.31.01] CIRCULATING PROGENITOR CELLS IN HYPERTENSION: EFFECTIVENESS OF A TREATMENT WITH OLMESARTAN IN IMPROVING CELL NUMBER AND MIRS PROFILE BESIDES EXPECTED PHARMACOLOGICAL EFFECTS. (September 2016) - Mandraffino, G.; Aragona, C.O.; Quartuccio, S.; Cairo, V.; Mamone, F.; Sardo, M.A.; Saitta, A.; Imbalzano, E.
Abstract : Objective: CD34+ circulating progenitor cells (CD34+CPCs) are a population of multipotent spare cells able to delay the development of atherosclerosis and cardiovascular disease (CVD) in conditions of increased CV risk. Increased reactive oxygen species (ROS), a common feature of CV risk factors including hypertension, may be toxic for cells. MicroRNAs (miRs) 221 and 222 have been shown to participate in differentiation and proliferation of CD34+CPCs, inhibiting cell migration and homing; miR221/222 are increased and associated with cell number and ROS in CD34+CPCs from hypertensive patients without additional risk for CAD. Moreover, miR221/222 modulate different genes regulating angiogenesis and inflammation. The aim of the present study was to evaluate whether in hypertensives a treatment with olmesartan may modify the number of CD34+CPCs and the levels of miR221/222 and ROS. Design and method: We evaluated CD34+CPC number, intracellular miR221/222 and ROS levels, arterial stiffness and echocardiographic indices at baseline (T0) and after a six-months treatment with olmesartan, 20 mg/die (T1) in 57 hypertensives with no additional risk factor for CAD, and in 29 healthy controls (baseline); fibrinogen, CRP, glucose and lipid profile were also evaluated. Results: At T1, systolic and diastolic blood pressure, ROS and miR221/222 were significantly decreased (all p < 0.001) with respect to T0, and cell number was increased (p < 0.001). CRP and fibrinogen levels also were reduced (p < 0.001), as were arterial stiffness indices. Conclusions: Olmesartan is effective in reducing miRs and ROS levels in CD34+CPCs from hypertensives, as well as in increasing CD34+CPC number, besides its expected pharmacological effects.